Production of bioethanol from sugarcane bagasse using cellulase enzyme - Rulianah Sri; Adani Putri Shabrina; Prayitno; Candra Dewi Listiyana; Zaky Aldillah Ahmad (E3S Web of Conferences)
Sugarcane bagasse has a high lignocellulose content, namely cellulose content 32–55%, hemicellulose 26.7–32%, and lignin 19–24%. With this content, sugarcane bagasse has good potential to be used as raw material for bioethanol production. In this study, commercial cellulase enzymes were used for the bagasse hydrolysis process. The purpose of this study was to determine the best conditions from variations in the addition of cellulase enzymes and fermentation time on the levels and yield of bioethanol using SSF process in a fermentor. This research was conducted with the following stages: pre-treatment; delignification; analysis of lignocellulose; SSF process; analysis of ethanol content. In this study, the varied factors were the inclusion of 3 and 3,5% (v/v) of cellulase enzymes and the duration of fermentation, from 3, 4, 5, 6, and 7 days. The results of this study showed that the addition of 3.5% (v/v) enzyme and fermentation for 7 days were the best conditions, the ethanol content obtained was 2.64%, and the yield was 14.78%. In this study, the hydrolysis process only used a single cellulase enzyme, and it turned out to produce a lower product when compared to using crude cellulase enzymes using Phanerochaete chrysosporium.